Enhancing efficiency of CdS/TiO2 nanorod arrays solar cell through improving the hydrophilicity of TiO2 nanorod surface - Shen, Q.; Xue, J.; Liu, Jian; Liu, X.; Jia, H.; Xu, B. (Elsevier BV * North-Holland, 2015)
CdS nanoparticles with well-defined crystallinity were assembled on vertically aligned TiO2 nanorod arrays (TiO2 NRAs) to form CdS/TiO2 NTAs heterostructures by cyclic voltammetry electrochemical deposition. The morphology and structure of CdS/TiO2 NTAs heterostructure were investigated by using X-ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The results show that the amount of CdS nuclei on TiO2 surface and the bond between CdS nuclei and TiO2 nanorod were improved by increasing hydrophilicity of TiO2 nanorod surface, and well crystalline CdS nanocrystals were deposited on TiO2 nanorod (001) surface with good bonding between CdS nanoparticle and TiO2 nanorod. With increased hydrophilicity of TiO2 nanorod surface, the Jsc, Voc and te of CdS/TiO2 NRAs heterostructure were increased. Especially, PEC (2.29%) was increased by near three times. This is because that CdS nanoparicles were uniformly dispersed on TiO2 NRAs and had good bond with TiO2 nanorods.